Front-end versión 2.0 para el inventario in-situ como herramienta del proyecto de investigación “Dinámica de crecimiento y servicios ecosistémicos del arbolado urbano de la ciudad de Loja” - Toledo Iñiguez, Carmen Azucena (2024)
The conduction of an in-situ inventory of trees in urban environments is presented as a valuable tool for dendrometric projects, which focus on measuring the physical and biological properties of trees. In the local context of the city of Loja, a study entitled "Dynamics of growth and ecosystem services of urban trees in the city of Loja" was carried out, where a prototype version of the application was developed, which fell into disuse due to various problems identified. Considering this background, the need arose for the development of a new mobile application in order to address current requirements of the project. Therefore, the main objective of the present Curricular Integration Work (TIC) is to determine the degree of support provided by the front-end version 2.0 for the in-situ inventory as a tool for the aforementioned project. To guide the execution of the TIC, the Mobile-D methodology was used, divided into four phases: exploration, initialization, production, and stabilization. From which the system requirements were obtained, the application design, the development divided into phases and guided by tests, with the subsequent delivery of the system to the project stakeholders. Subsequently, to solve the question posed, the estimated usefulness of the technology acceptance model (TAM) was used; with which it was determined that the mobile application provides a high degree of support for the in-situ inventory as a tool for the research project. Keywords: Flutter, Mobile-D, clean architecture, TDD, TAM, qr trees.